The, of, in, the, of, from, the The Position of Murtad's Widow in the Distribution of Inheritance from the Testator (Husband) - Qisthina Armalia Hirzi; Ani Setiawati; Afdol (Hang Tuah Law Journal, 2020)
The research with the title of "The Position of Murtad’s Widow in the Distribution of Inheritance from the Testator (Husband)", with the problem of an apostate wife, so that it is necessary to question the right of an apostate widow to the inheritance of the testator (husband), related to the obligatory will. Research based on legislation and case studies can obtain a conclusion that obligatory wills are known in Islamic law given to people who are not the heirs because there is no blood relationship with the testator or because he is an heir but for some reason, it is not recognized as an heir of the inheritance. People who have close relations with the testator but are not heirs because there is no blood relationship with the heir, including the adopted child. Widows according to Islamic Law Compilation Book are the heirs, although not because of blood relations, if the widow is an apostate, then she is not as an heir, therefore the widow gets a part of the heir's assets but in the form of a mandatory will.